MEMBANGUN IDENTITAS SISWA MELALUI PEMBELAJARAN PPKn YANG BERBASIS KEARIFAN LOKAL DI SMA SWASTA DHARMA UTAMA SUKASARI - Nuria Andini; Abdul Marif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to build student identity through local wisdom-based Civics learning, knowing the supporting and inhibiting factors in building student identity and analyzing the role of teachers in building student identity through local wisdom-based Civics learning. This research uses a qualitative approach with descriptive data analysis. The data sources in this study were obtained from direct interviews with students and Civics teachers at SMAS Dharma Utama Sukasari. This research data collection uses interview methods, observation and documentation. The data analysis technique used is data grouping, identified, described, and analyzed one by one to get the desired results and be able to draw conclusions from the data. The results showed that the application of local wisdom-based Civics learning was able to improve students' understanding of local cultural values. Students not only know, but also internalize local cultural values in their daily lives. Supporting factors found include full support from the school, active involvement of teachers in the learning process, and student enthusiasm. The inhibiting factors identified include limited resources and learning materials, as well as the lack of training for teachers in integrating local wisdom in learning. The conclusion of this research is that local wisdom-based Civics learning is very effective in building students' identity